What Should Doctors Know? - Daniele, Franca (European Scientific Journal, ESJ, 2021)
ract Delors has established some of the pilasters of education that include learning to know, learning to do, learning to be, and learning to live together and that can be applied to medical school students. More specifically, knowledge is the first important skill students must develop in order to start becoming doctors. The present paper, considering exclusively medical degree courses, focuses on assessing the different educational English language needs of medical students and investigates to what extent such needs are satisfied. To address these issues, a survey was carried out using the Internet to look into all the different Italian universities and to see what each of them offers in terms of English language teaching. English courses in Italian medical schools as they appear today from the present survey seem to be useless. They cannot fulfill the particular needs of medical school students and even less of medical doctors. A unified program is necessary for all Italian medical schools, and English should be taught through specific pathways for each individual student.